High-Resolution Transcranial Electrical Simulation for Living Mice Based on Magneto-Acoustic Effect - Zhou, Xiaoqing; Liu, Shikun; Wang, Yuexiang; Yin, Tao; Yang, Zhuo; Liu, Zhipeng (Frontiers in Neuroscience, 2019)
Transcranial electrical stimulation is an important neuromodulation tool, which has been widely applied in the cognitive sciences and in the treatment of neurological and psychiatric diseases. In this work, a novel non-invasive method of transcranial electrical stimulation with high-resolution transcranial magneto-acoustic stimulation (TMAS) method has been tested experimentally in living mice for the first time. It can achieve spatial resolution of 2 mm in the cortex and even in the deep brain regions. The induced electrical field of TMAS was simulated and measured using a test sample. Then, an animal experimental system was built, and the healthy as well as Parkinson’s disease (PD) mice were simulated by TMAS in vivo. To investigate the effect of transcranial ultrasound stimulation (TUS) at the same time as TMAS, a TUS group was added in the experiments and its results compared with those of the TMAS group. The results not only demonstrate the high-resolution ability and safety of TMAS, but also show that both TMAS and TUS improved the synaptic plasticity of the PD mice and might improve the spatial learning and memory ability of the healthy mice and the PD mice, although the improvement performance of the TMAS group was superior to that of the TUS-group. Based on the in vivo TMAS studies, we propose that TMAS functions as a dual-mode stimulation combining the electric field of the magneto-acoustic effect and the mechanical force of TUS. Our results also provide an explanation of the mechanism of TMAS. This research suggests that future use of US stimulation in magnetic resonance imaging (MRI)-guided studies should involve careful consideration of the induced magneto-acoustic electrical field caused by the static magnetic field of MRI.